Correlates and outcomes related to periprocedural myocardial injury during percutaneous coronary intervention for chronic total occlusion: Results from a prospective, single center PCI registry. (10th February 2016) - Zhang, Qi; Hu, Jian; Yang, Zhen Kun; Ding, Feng Hua; Zhang, Jian Sheng; Du, Run; Zhu, Tian Qi; Shen, Wei Feng; Kirtane, Ajay J.; Zhang, Rui Yan
Abstract : Background: There is increasing interest in percutaneous coronary intervention (PCI) for chronic total occlusions (CTO). Periprocedural myocardial injury (PMI) post CTO PCI is not uncommon, but true incidence and implications of PMI are not well understood. Objectives: This study aimed to investigate risk factors for PMI post CTO PCI and its implications for the 1‐year clinical outcome of a Chinese population. Methods: Baseline characteristics, procedure features, and major adverse cardiac events (MACE) at 1 year were assessed in 629 consecutive patients who underwent CTO PCI. PMI was diagnosed as an elevation of creatine kinase MB ≥3 times ULN 12–24 hr post procedure. Multivariate analysis was performed to determine the correlates of PMI and MACE at 1‐year follow‐up. Results: In total, PMI was detected in 115 patients (18.3%). Compared with patients without PMI, those with PMI had a higher percentage of previous coronary artery bypass grafting (CABG), right coronary occlusion and side branch occlusion, and technical success was lower in the PMI group (90.4% vs. 96.7%, P  = 0.003). One‐year MACE‐free survival was reduced in the PMI group (87.8% vs. 95.9%, P  = 0.001). The final TIMI flow 0–1 (OR 2.23, 95%CI 1.06–4.87, P  = 0.02), side branch occlusion (OR 2.67, 95%CI 1.19–7.11, P  = 0.009), retrograde PCI (OR 1.35, 95%CI 1.10–2.74, P  = 0.04), and history of prior CABG (OR 2.41, 95%CI 1.38–5.91, P  = 0.01) were independent risk factors for the occurrence of PMI. Conclusions: In this unique Chinese cohort, PMI post CTO PCI was associated with several clinical and angiographic factors and exerts an adverse effect on 1‐year clinical outcomes. © 2016 Wiley Periodicals, Inc.